Professional image and identity in the construction of nursing knowledge (Revista Latino-Americana de Enfermagem, 2002)
Based on a historic qualitative study using documental analysis, we searched dispersions in the construction of knowledge in articles published in the Anais do Congresso Brasileiro de Enfermagem (Proceedings of the Brazilian Nursing Congress) from 1977 through 1987. Dispersions emerged as categories that repeated themselves as subjects of note or as small punctuations. Our analysis converged into two main categories: professional image and professional identity. These categories took the shape of a complex and dynamic network, in which there were two explicit sub-categories: professional status and professional role.